Analisis Kinerja Mesin Grate Cooler Tipe CFG Kapasitas 321 Ton/Jam Pada Proses Produksi Clinker Berdasarkan Efisiensi Thermal - Muhammad Adib Arifin; Ratna Dewi Anjani (Jurnal Serambi Engineering, 2024)
This research aims to analyze the performance of a CFG type grid cooler in the clinker cooling process with a capacity of 321 tons per hour in the cement industry. The analysis focused on the thermal efficiency of the engine to identify potential operational efficiency improvements. Research methods include heat balance, mass balance measurements and evaluation of heat loss in the cooling process. It is hoped that the results of this research can provide guidance in optimizing the operation of grate cooling machines, improving the quality and energy efficiency of clinker produced in the cement industry.